Global discourse of restorative justice studies: an analysis of three decade bibliometric analysis (1993-2022) - Gustina, Amelya (Contemporary justice review, 2023)
This study aimed to analyze the bibliometric characteristics of Restorative Justice (RJ) articles published in Scopus-indexed journals for the last three decades (1993–2022). We conducted a bibliometric and content analysis of publications in the Scopus database, and then 2,453 publications obtained from the Scopus database were analyzed and visualized using VOSViewer. The results show that RJ is a topic that continues to grow and has been of concern to researchers worldwide since the 1990s: 1993–2003 (159 publications) increased to 2,294 publications (total publications) by the end of 2022. We have divided the period studied into three groups of ten years; the first period (1993–2002) was dominated by the development of the theory of RJ, such as challenges of RJ, considering RJ, and communities, victims, and offender reintegration. In the second period (2003–2012), articles emerged regarding the effectiveness of RJ practices, retributive and RJ, and several implementation practices. Then the third period (from the 2010s to the early 2020s), more topics discussed the implementation of RJ, including an overview of philosophy to practice.